Assessing the Effectiveness of the Enforcement Mechanisms for Electoral Offenses in Indonesia - Mantali, Rinoldi (Estudiante Law Journal, 2025)
This study aims to assess the effectiveness of enforcement mechanisms for electoral offenses in Indonesia. The main issues examined are the extent to which the current system can effectively address violations and the challenges faced in its implementation. This research adopts a socio-legal approach using qualitative methods, including literature review, legal analysis, and case studies of electoral violations. The findings reveal that the enforcement system continues to face several obstacles, such as overlapping institutional mandates (between Bawaslu, the police, and the prosecution), limited resources, and weak coordination and consistency in applying sanctions. These factors contribute to a lack of deterrent effect, allowing violations to persist across election cycles. The study recommends strengthening inter-agency coordination, restructuring the legal framework, and enhancing institutional capacity to establish a more effective and credible enforcement system for electoral justice.